Litteraturläsning som upplevelse och livskunskap - Pär-Yngve Andersson (Dalarna university, 2021)
In this essay, I propose that teachers should be made aware of the value of positive reading experiences and recognize these experiences as the basis for literature education. Indeed, pupils' reading experiences should be placed in the foreground, and ideas relating to literary form should be considered mainly in relation to examples of how passages from the literary work are, say, moving or thrilling. The essay is not based on empirical data, but on my long and varying experience as a teacher, researcher and literary critic. I draw on researchers and authors who explain what makes reading valuable. One such value that I emphasise is that readers sometimes seem to meet their own selves in literary works, but also that which is different or new. The individual perspective can be broadened or transformed after reading texts that seem unfamiliar in some ways. Such experiences, I argue, have intrinsic values, and so do strong feelings of pleasure or consolation that literature stimulates. Moreover, the personal and the social are intimately linked. I emphasize that in order for literature to become an even more important part of a social world, politicians as well as teachers must realize that literature lessons must be more than instruments for descriptors, marks or exams. When it comes to teaching and learning, quality is determined by what happens in the classroom, and not by objectives stipulated in national or local documents.